2019
DOI: 10.1080/13636820.2019.1644364
|View full text |Cite
|
Sign up to set email alerts
|

Does implementation of competence-based education mediate the impact of team learning on student satisfaction?

Abstract: Competence-based education (CBE) is an innovation in (vocational) education aimed at improving students' competences. Little is known, however, about the processes leading to successful implementation of CBE and about its outcomes. This study investigates the effects that the level of CBE implementation has on student satisfaction (regarding the quality of education, guidance, and the development of interpersonal and general vocational skills) and to what extent CBE implementation mediates the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…Students are also required to reflect on their own learning process and increasingly steer their own learning" (van Griethuijsen et al 2019, 3). Van de Griethuijsen et al (2019) investigated the effects that the level of Competence-based Education (CBE) implementation had on student satisfaction and the influence of CBE implementation in the relationship between teacher team-learning activities and student satisfaction. The results revealed that teacher team-learning was positively associated with the implementation of CBE and that CBE had a positive effect on student satisfaction, so it was concluded that the implementation of CBE had fulfilled its goal of better preparing students to enter the work market and that teacher team-learning could support the further implementation of CBE.…”
Section: Implementation Of Transversal Competences In Vet Modelsmentioning
confidence: 99%
“…Students are also required to reflect on their own learning process and increasingly steer their own learning" (van Griethuijsen et al 2019, 3). Van de Griethuijsen et al (2019) investigated the effects that the level of Competence-based Education (CBE) implementation had on student satisfaction and the influence of CBE implementation in the relationship between teacher team-learning activities and student satisfaction. The results revealed that teacher team-learning was positively associated with the implementation of CBE and that CBE had a positive effect on student satisfaction, so it was concluded that the implementation of CBE had fulfilled its goal of better preparing students to enter the work market and that teacher team-learning could support the further implementation of CBE.…”
Section: Implementation Of Transversal Competences In Vet Modelsmentioning
confidence: 99%
“…Competence-based education (CBE) is a kind of innovation in vocational education with the goal of being better transition of the students from school environment into the work environment that will be faced by vocational school students after graduation. The need of CBE exists because the vocational school graduates have enough knowledge, but less in attitude and skills needed in work place [12]. Workers should have good characteristics and good habits, such as discipline, positive attitude toward works, high commitment toward jobs, honesty, the skill of collaboration to work in groups to overcome complex job problems, good communication skills, and open mind for change.…”
Section: Resultsmentioning
confidence: 99%
“…Workers should have good characteristics and good habits, such as discipline, positive attitude toward works, high commitment toward jobs, honesty, the skill of collaboration to work in groups to overcome complex job problems, good communication skills, and open mind for change. Competence based education is one of the way to make better transition of the graduates of vocational school to work place by focusing on the integration of knowledge, skill, attitude and pressing on creating real learning environment [12] If the technical skills of the vocational school graduates does not be used in the work place, employer needs the soft skills that the graduates have as the outcome of training in vocational school, to involved actively in production process.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing relevant literature Kris & Yvonne, 2014;Williams, Moser, Youngblood & Singer 2015;Richard & Bedard-Vorhees, 2016;Fowler, 2018;Parson, Childs, & Elzie, 2018;McDonald, 2018;Sturgis & Casey, 2018;Egbert & Shahrokni, 2019;Ralf, et al, 2020;among others)…”
Section: Key Principles Of Competency-based Learningmentioning
confidence: 99%